INVENTORY OF DRAGONFLIES AND DAMSELFLIES (ODONATA) IN ANDALAS UNIVERSITY’S LIMAU MANIS CAMPUS COMPLEX, PADANG: USING PHOTOGRAPHICAL APPROACH - Muhammad Nazri Janra (Jurnal Natural, 2018)
Odonata, which consists of true dragonflies and damselflies, is considerably understudied in Sumatra, especially in West Sumatra region. While the campus area of Andalas University in Limau Manis provides many suitable habitats for dragonflies and damselflies, the least has been done in learning these organisms. In this paper, we intend to conduct the inventory of Odonata in Limau Manis area by using photography approach (by taking decent pictures only, without sampling the animal). After spending 14 days of data collection which spanned from October 2017 until February 2018), we listed 27 Odonata species. Of which, 11 species belong to four families under suborder Zygoptera and 16 species grouped into four families under suborder Anisoptera. Libellulidae is a family under Anisoptera that was found with most species members. Photography approach promises an immense help in doing species inventory for this animal group for its reliability in determining species identification without harming species’ population.Keywords: damselflies, dragonflies, Libellulidae, Limau Manis area, photography approach